Stages of Formation of International Legal Regulation Investment Activity - Ramazanovna, Kuzieva Nargiza (Researchparks Publishing, 2023)
This article examines the development of international legal regulation of investment activity, the emergence of the first investment relations, the stages of development of investment activity and the classification of investment activity. And also the modern stage of development of international legal regulation of investment activity of the country is considered.